PODCAST WITH GROUP DISCUSSION IMPACTS ON STUDENTS' WRITING DISCUSSION TEXT - Firza Galuh Drajati; Siti Musarokah; Sri Wahyuni (Esteem Journal of English Education Study Programme, 2025)
This research explored the effectiveness of integrating podcasts into group discussions to enhance students’ ability to write discussion texts. Despite the recognized importance of writing for academic success, many students found it challenging to construct well-organized and coherent argumentative essays due to a lack of engagement and limited exposure to diverse perspectives. To overcome this issue, a six-week intervention was conducted involving thirty-three eleventh-grade students at SMA N 1 Cepiring, employing a one-group pre-test and post-test experimental design. The influence of the combined use of podcasts and group discussion was measured through paired-samples t-tests, comparing students’ writing performance before and after the intervention. The findings revealed a significant improvement in students’ skills in producing logically structured and cohesive discussion texts following the treatment.